Relação entre queixa de memória, alterações cognitivas, vulnerabilidade física e teste de dupla tarefa em idosos - Dalpubel, Daniela (2017)
Introduction. The memory complaint (MC) reflects the perceptions and the evaluation of the memory by the participant or an informant that knows him/her well. It is very common in the elder. Studies suggest that can exist association between MC and cognitive alterations, in these cases, it could be supposed that physical vulnerability can even increase it. Objective. Investigate the relation between MC in elders that has cognitive alterations and physical vulnerability. Method. It is a cross-sectional study, quantitative and correlational. There were evaluated 100 participants with age starting from 65 years by the Memory Complaint Scale (MCS), Addenbrooke’s Cognitive Exam Revised (ACE-R), Mini-Mental State Examination (MMSE), Vulnerable Elders Survey (VES-13), Geriatric Depression Scale (GDS) and the sociodemographic questionnaire. Results. The participants were divided into two groups according to SMC-A and B. Regarding the sociodemographic variables, the groups were divided similarly. In both groups the sample was composed by a majority of women, education had a median of 4 years, and age median of 72 years. It wasn't verified association between MCS form A or B and VES-13. It was found a significant statistical difference between MCS form A and MMSE, between MCS form B and ACE-R total points and MCS form B and all ACE-R domains. The most evident associations between MC and cognitive alterations were found in MCS form B. Conclusion. The report of the informant about the elder's MC has a wide positive correlation with the cognitive screening tests.